PEMANFAATAN BUAH NAGA MERAH DAN KELOPAK ROSELLA DALAM PEMBUATAN VELVA - Adi Darman Damanik; Raswen Efendi; Vonny Setiaries (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to getthe best combination of dragon fruit combined with rosella petals. This research used a Completely Randomized Design (CRD) with five treatments and three replication andfollowed by Duncan’s New Multiple Range Test (DMNRT) at level of 5%. The treatmentswere NR1 (the ratio dragon fruit : rosella petals 3:1) , NR2 (the ratio dragon fruit: rosella petals 2: 1), NR3 (the ratio dragon fruit: rosella petals 1: 1), NR4 (the ratio dragon fruit: rosella petals 1: 2), and NR5 (the ratio dragon fruit: rosella petals    (1: 3). The results showed that the ratio of dragon fruit and rosella petalsin making velva significantly affected to degrees of overrun, pH, melting time, fibers content, and sensory assessment includes of the colour, flavor, taste, and texture  the velva producted. The best treatment of making velva was NR1(the ratio of dragon fruit: rosella petals 3: 1) which had fiber content 1.63%, overrun velva 22.56%, melting range time 16.62 minutes, pH 5.14, antioxidant 137.71 ppm. The treatment NR1 haspurple color  (4,64), dragon fruit flavor (3,80), dragon fruit taste(4,04), soft texture (2,92), and overall liked by panelist (2,58). Keywords: velva, fruit dragon, petals rosella